Chronic exposure to amoxicillin and its effects on growth, immunity, organ function and residue accumulation in mice (Asian Journal of Medical and Biological Research, 2025)
Antibiotic therapy is essential in human and veterinary medicine, but resistance and prolonged exposure to antibiotic residues pose significant risks to health. This study investigated the long-term effects of amoxicillin residue on Swiss Albino male mice. Mice (n=20) were divided into control (no antibiotics) and treated (amoxicillin at the rate of 10 ppm in drinking water for one year; MRL 0.01 ppm) groups. Body weight, physical condition, immune status, blood parameters, ALT and AST enzyme levels, histopathology and residue accumulation in organs was examined. Antibiotics-treated mice exhibited significant weight gain (P